Effect of Dynamic Flexural Strength on Impact Response Analysis of AlN Substrates for Aerospace Applications - Zhen Wang; Yan Liu (Aerospace)
Electronic devices play an extremely important role in the aerospace field. Aluminum nitride (AlN) is a promising ceramic material for high-reliability electronic packaging structures that are subjected to impact loads during service. Quasi-static and dynamic flexural tests were conducted to determine the rate-dependent flexural strengths of AlN ceramics. The impact response of the AlN substrates was investigated using experimental tests and a smeared fixed-crack numerical model. The critical velocity of the impactor and the failure mode of the ceramic plate can be accurately predicted using the Drucker–Prager criterion with the scaled fracture-strength parameter. The radial cracks on the ceramic plate upon impact were well reproduced via the proposed novel numerical technique, showing better accuracy compared to the widely used Johnson–Holmquist II (JH-2) model. The effect of impactor nose shape and deflection angles were further investigated to better illustrate the low-velocity impact response of AlN ceramic substrates. Based on the dynamic flexural-strength testing results, this study achieves the prediction of low-speed impact response for AlN ceramic structures, thereby providing technical support for the impact reliability analysis of aerospace ceramic-packaging devices.